2020
DOI: 10.1016/j.chest.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The First Description of Asthma Due to Heart Conditions in the History of Medicine

Abstract: Asthma has frequently been described in historical textbooks over the centuries. The word "asthma" is derived directly from the Greek word άsqma, meaning a shortdrawn breath or panting. 1 In the Middle Ages, numerous Greek books, including medical books, were translated into Arabic, in which asthma is defined as al-Rabw. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“… 123 Avicenna assumed and demonstrated that some natural medicaments have the capacity to help other treatments by directing them towards specific body organs. 124 , 125 In view of that, Avicenna suggested the combination therapy of a cardiac medicine with Lemon balm ( Melissa officinalis L.) or Behmen ( Centaurea behen L.). 122 The com­parison of herbal medicines used in studying HTN in different regions of Iran has indicated that different parts of Iran use diverse plants to treat this disorder.…”
Section: Medicinal Plants Used For the Treatment Of Htn In Iranmentioning
confidence: 99%
“… 123 Avicenna assumed and demonstrated that some natural medicaments have the capacity to help other treatments by directing them towards specific body organs. 124 , 125 In view of that, Avicenna suggested the combination therapy of a cardiac medicine with Lemon balm ( Melissa officinalis L.) or Behmen ( Centaurea behen L.). 122 The com­parison of herbal medicines used in studying HTN in different regions of Iran has indicated that different parts of Iran use diverse plants to treat this disorder.…”
Section: Medicinal Plants Used For the Treatment Of Htn In Iranmentioning
confidence: 99%